CREBBP inactivation sensitizes B cell acute lymphoblastic leukemia to ferroptotic cell death upon BCL2 inhibition - Alicia Garcia-Gimenez; Jonathan E. Ditcham; Dhoyazan M. A. Azazi; George Giotopoulos; Ryan Asby; Eshwar Meduri; Jaana Bagri; Nathalie Sakakini; Cecile K. Lopez; Nisha Narayan; Tumas Beinortas; Shuchi Agrawal-Singh; et al. (Nature Communications)
Abstract B-cell acute lymphoblastic leukemia (B-ALL) is a leading cause of death in childhood and outcomes in adults remain dismal. There is therefore an urgent clinical need for therapies that target the highest risk cases. Mutations in the histone acetyltransferase CREBBP confer high-risk and increased chemoresistance in ALL. Performing a targeted drug-screen in isogenic human cell lines, we identify a number of small molecules that specifically target CREBBP-mutated B-ALL, the most potent being the BCL2-inhibitor Venetoclax. Of note, this acts through a non-canonical mechanism resulting in ferroptotic rather than apoptotic cell death. CREBBP-mutated cell lines show differences in cell-cycle, metabolism, lipid composition and response to oxidative stress, predisposing them to ferroptosis, which are further dysregulated upon acquisition of Venetoclax resistance. Lastly, small-molecule inhibition of CREBBP pharmacocopies CREBBP-mutation, sensitizing B-ALL cells, regardless of genotype, to Venetoclax-induced ferroptosis in-vitro and in-vivo, providing a promising drug combination for broader clinical translation in B-ALL.